Role of B-Schools in enhancing learnability and employability - Srinivas, Prof. Ved; Rani, Dr. Ridhi; Reddy, Dr. A. Jagan Mohan (The journal of contemporary issues in business and government, 2022)
India is set to become the world’s youngest country with 64% of its population in the working age of 20-59 by 2020(19). This demographic dividend offers India an unprecedented edge & could add a significant 2% to the GDP growth rate. The country needs a productive workforce that can make a significant contribution to India’s economic development. With employability posing a major challenge and the kind of disruption that’s taking place across the world, lifelong learning seems to be the only way to stay employable in the future. Learnability is something, which everyone needs to emulate and practice i.e. youngsters need to increase their learnings; educators need to update themselves on a continuous basis and employers need to measure and facilitate learning by their employees. With the recent Covid-19 Global Pandemic, it is set to disrupt the conventional classroom teaching and open up new vistas for Learnability. Skills development and employment generation are critical factors from a sustainability viewpoint. Hence, B-schools in particular & other stake holders in general need to pay attention to this aspect on priority, lest the promising advantage of demographic dividend might wither away. The purpose of the paper is to look at the concept of Learnability, its importance and its impact on employability. Secondly what’s that B- schools need to do to improve Learnability. In the process, the authors also look some of the B- schools & their various initiatives taken in this regard. This is purely an exploratory study based on secondary data, review of literature and expected to emphasize on the importance of Learnability.